Beam Tailoring Devices Using Transmission-Type Subwavelength Grating - Gang Wu; Shanglin Hou; Jingli Lei; Zuyong Yan (Photonics, 2023)
Subwavelength gratings (SWGs) possess an excellent ability to manipulate the wavefronts of light waves. We investigated the beam tailoring mechanism of aperiodic SWGs in our current work, and a bifocal lens, a beam splitter, and a beam combiner based on transmission-type one-dimensional SWGs are presented and simulated here. By designing grating nanobar parameters to meet the predetermined phase shift profile of the diffraction light, desired beam steering is accurately achieved for the three devices while maintaining high transmissivity. All the simulated results show good agreement with the theoretical predictions.